Ab-initio simulations of magnetic iron sulphides - Wright, Kathleen; Wells, S.; Alfe, A.; Blanchard, L.; Brodholt, J.; Catlon, R.; Calleja, M.; Price, D.; Tyler, R. (Taylor & Francis Ltd, 2005)
We present the results of simulations, using density functional theory (DFT) with generalized gradient corrections (GGA), on the troilite (FeS), pyrrhotite (Fe12xS) and MnP phases of FeS. The values obtained for the cell parameters and c/a ratio of troilite accurate to within 1% of those determined by experiment, a significant improvement on previous simulations. Energy volume curves for FeS in the troilite and MnP structures indicate a pressure-induced transition at 4 GPa (experimentally observed at 3.4 GPa). Comparison of spin-polarised and non-spin-polarised simulations of the troilite structure demonstrate the significance of magnetostructural effects in determining the c/a ratio and shed light on the magnetic and volume collapse of FeS on its transition from the MnP to a monoclinic structure at 6.7 GPa. Simulations of different (001) surface terminations of troilite indicate that stable surfaces are characterised by triangles of iron atoms "capped" with a sulphur atom.